Perilaku Reaksi Harga dan Volume Perdagangan Saham terhadap Penumuman Dividen - Bandi, Jogiyanto Hartono (IIAKAP, 2000)
Many of researches on price and volume reaction associated with the earnings announcement have been conducted. Bamber and Cheon (1995) acknowledge that three is a positive relation between the average of magnitudes of price and of volume reaction. Nearly a quarter of the quarterly earning announcements generate price and volume reaction of different realtive magnitudes. Surprisingly, there is little empiricul evidence of such reaction regarding the dividend announcements. This research investigates the volume and price reactions associated with the devidend announcements. The result of this study shows a dependence between price and volume reaction,. Additionally, price and trading volume is positively related. Although there is a relation between price and volume reaction around deviden announcements, the reactions are very relatively different in magnitudes. the realitve magnitudes of price and volume reactions are extremely different for 32,88 percent of these sample devidend announcements, relatively indeterminate reactions.